NO donors exhibit anti-inflammatory properties by modulating inflammatory signatures and by regulating the life cycle of dendritic cells. Issue 6 (11th October 2017) - Ripamonti, Chiara; Papagna, Angela; Storini, Claudio; Miglietta, Daniela; Foti, Maria
Abstract : Nitric oxide donors originated from ferulic acid moiety modulate the inflammatory program and cellular life cycle, but not the T cell stimulatory capacity of DCs. Abstract: NO mediates a variety of physiologic processes and is considered an important intracellular messenger in different cellular systems. Because of its complex regulation and multiple molecular and cellular targets, NO provides both stimulatory and suppressive properties in the immune system. Dendritic cells (DCs) are considered the most potent APCs, whose regulation has important implications in the induction of an effective immune response. In this study, we analyzed the effect of the compound NCX 2057, a new class of NO-releasing derivatives of ferulic acid, on activation and functional properties of DCs. NCX 2057 was able to modulate the inflammatory program, the cytokines production, and the cellular life cycle but not the maturation markers and the T cells stimulatory capacity of DCs in the presence or absence of LPS. The results indicate that NCX 2057 may modulate different aspects of the activation of DCs and suggest novel applications of NO donors in the contest of inflammatory response modulation through the life cycle regulation of DCs.